Persepsi Iklim Sekolah dan Kesejahteraan Subjektif Siswa di Sekolah - Prasetyo, Ridwan Aji Budi (Jurnal Psikologi Teori dan Terapan, 2018)
Abstract: This study aimed to investigate the relationship between perception of school climate and studentâs subjective well-being at school. Two instruments were used to collect data, namely (1) Scale of Subjective Well-Being at School, which was developed based on Osgoodâs semantic differential mode; and (2) Scale of Perception of School Climate which was constructed based on Likertâs summated rating model. Ninety senior high school students participated in this study. They were selected by means of convenience sampling method. Multivariate correlation technique (MANOVA) was then applied to examine the correlation between the two constructs. The result revealed that there is a significant positive correlation between perception of school climate and studentâs subjective well-being at school (F = 11.561, Partial Eta Square = 0.210, and p = 0.00 (p < 0.01)). Meanwhile, perception of school climate has significant positive correlation with both cognitive and affective aspects of subjective well-being, with the value of correlation coefficient tends to be higher with cognitive aspect than with affective aspect.Keywords: School climate, subjective well-being, school, studentAbstrak: Penelitian ini bertujuan untuk melihat hubungan antara persepsi terhadap iklim sekolah dengan kesejahteraan subjektif siswa di sekolah. Dua skala disusun untuk pengumpulan data, yaitu: (1) Skala Kesejahteraan Subjektif di Sekolah, yang disusun berdasarkan model semantic differential Osgood dan (2) Skala Persepsi Iklim Sekolah, yang disusun berdasarkan model summated rating Likert. Sembilan puluh siswa berpartisipasi dalam penelitian ini. Sampel tersebut dipilih dengan teknik convenience sampling. Teknik korelasi multivariat (MANOVA) kemudian digunakan untuk menilai korelasi antara kedua konstruk tersebut. Hasil penelitian ini mengungkapkan bahwa terdapat korelasi positif yang signifikan antara persepsi terhadap iklim sekolah dengan kesejahteraan subjektif siswa di sekolah (F = 11.561, Partial Eta Square = 0.210, and p = 0.00 (p < 0.01)). Sementara itu, persepsi terhadap iklim sekolah memiliki korelasi positif yang signifikan dengan aspek kognitif dan afektif dari kesejahteraan subjektif siswa di sekolah, dengan kecenderungan lebih tinggi pada aspek kognitif dibandingkan pada aspek afektif.